Granular cell tumour of the colon with extensive sclerosis. Issue 7 (July 2016) - Chelliah, Adeline; Kalimuthu, Sangeetha; Szentgyorgyi, Eva; Chetty, Runjan
Abstract: Granular cell tumour (GCT) is a rare, usually benign, mesenchymal lesion that can occur in nearly any organ, but has a proclivity for the oral cavity, skin and subcutaneous tissue. They occasionally arise in the gastrointestinal tract (GIT) where the oesophagus is most commonly involved. Occurrence in the colorectum is unusual. We report a case of a 73 year-old man with an incidentally discovered GCT with extensive sclerosis in the caecum. Microscopically, a well-circumscribed, paucicellular nodule was identified in the submucosa with prominent hyalinisation and focal myxoid change. Scattered, finely granular cells expressing S100, inhibin and calretinin were identified. CD117 and DOG-1 were negative. This case was made challenging by the prominent sclerosis with only focally visible granular cells, however, the overall features were those of a GCT of the colon. We highlight the morphological and immunohistochemical features of this rare entity in the colon, and discuss the differential diagnosis. In this era where incidental polyps and submucosal lesions are increasingly being detected by endoscopy, knowledge and recognition of GCT in the colon is important as they are generally benign with a good prognosis following complete excision.